Site-Specific Infrared Probes of Proteins - Ma, Jianqiang (Annu Rev Phys Chem, 2015)
Infrared spectroscopy has played an instrumental role in studying a wide variety of biological questions. However, in many cases it is impossible or difficult to rely on the intrinsic vibrational modes of biological molecules of interest, such as proteins, to reveal structural and/or environmental information in a site-specific manner. To overcome this limitation, many recent efforts have been dedicated to the development and application of various extrinsic vibrational probes that can be incorporated into biological molecules and used to site-specifically interrogate their structural and/or environmental properties. In this Review, we highlight some recent advancements of this rapidly growing research area.